EVALUASI KEBERLANJUTAN PENGELOLAAN PERKEBUNAN KELAPA SAWIT POLA INTI-PLASMA DI PT.PERKEBUNAN NUSANTARA VII MUARA ENIM, SUMATERA SELATAN (Evaluation and Status of Sustainable Palm Oil Management in PT.Perkebunan Nusantara VII Muara Enim, South Sumatera) - Ruslan -; Supiandi Sabiham; Sumardjo -; Manuwoto - (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2013)
There were three pilars of  palm oil plantation in Indonesia, state-owned large estates and private estates which total extensive oil palm plantations area in 2005 were 5.445 thausands  hectares with 12.452 thausands million tons production crude palm oil. The composition of the plantation farmers  area was 40,02 %, national large plantations was about  13,96 %, and  48,68  % for private estates.There are two types of Management of their field, nucleous estate smallholders  (NES) and farmers. Unfortunately farmers better than independent farmers in managing the  estates, because there was cooparation between the farmers with the nucleous companies. The PIR system stated that the nucleous  plantation companies were useful in developing and crops farmers market assigning, While the farmers must manage his estates well and market the results through the company's nucleous. Sustainability analysis conducted by the method of Multi Dimensional Scaling (MDS) approach  with Rap-Insus palm oil techniques (Rapid Appraisal-Index Sustainability of palm oil Management). Analysis of key factors of sustainability management performed a prospective analysis of the sensitivity factors (leverage factor) of the MDS and the factors from the analysis of stakeholders' needs. The results showed that the status of sustainability of palm oil management in   PT.Perkebunan Nusantara VII Muara Enim, South Sumatera)was quite sustainable with a multidimensional index of 67,67.